PENETAPAN KADAR TOTAL FLAVONOID EKSTRAK ETANOL KACANG MERAH (Phaseolus vulgaris L.) SECARA SPEKTROFOTOMETRI VISIBEL - Novena Yety Lindawati; Sabilla Hudzaifah Ma'ruf (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Red kidney bean is one of the string beans that contain highest-fiber with a concentration 26.3 gram/100 gram substance. Red kidney bean contains flavonoid tannin steroid/triterpenoid and coumarin. The Flavonoid in red kidney bean has anti-diabetes activity. This research aims to determine total flavonoid content in the red kidney bean extract. Extraction is done using the maceration method with 70% ethanol solvent. The extract which is got is used for qualitative and quantitative analysis. Quercetin used as a standard solution. The qualitative analysis of flavonoid using TLC, Wilstater Cyanidin by forming a red complex and NaOH by a forming yellow complex. The Quantitative analysis was using colorimetry method with reagent AlCl3 to form complexes between AlCl3 and keto groups. Quantitative analysis continued with Visible Spectrophotometry on a wavelength of 430.0 nm and operating time at the 27th minute. The results of the qualitative test showed that the extract was positive flavonoids. The average concentrations of total flavonoids were 0,4733% extract with a variation coefficient value of 1,2%.